Sanqi oral solution alleviates podocyte apoptosis in experimental membranous nephropathy by mediating EMT through the ERK/CK2-α/β-catenin pathway - Wang, Xiaowan; Wang, Juanjuan; Zheng, Bidan; Tian, Ruimin; Huang, Lihua; Mao, Wei; Feng, Yi; Liu, Bo; Xu, Peng (Frontiers in Pharmacology, 2025)
IntroductionSanqi oral solution (SQ) is a Chinese medicine that has been used well to treat idiopathic membranous nephropathy (IMN). It has been demonstrated to mitigate IMN proteinuria by inhibiting podocyte apoptosis. however, the precise mechanism has not been fully elucidated.MethodsA passive Heymann nephropathy (PHN) rat model was used to mimic the in vivo disease characteristics of IMN. The PHN rats were intragastrically administered SQ (12.6/6.3 mL/kg) or tacrolimus (0.315 mg/kg) for 21 days. SQ was applied to ADR-induced podocytes in vitro. The effects of SQ on IMN and its underlying mechanisms were determined by measuring biochemical indices, pathomorphological characteristics, membrane attack complex (MAC), cell morphology, and protein levels.ResultsThe SQ ingredients found in rat serum underscored their successful absorption in rats. In PHN rats, SQ induced a significant reduction in proteinuria, MAC, C5b-9, and glomerular basement membrane thickness, along with a drop in apoptotic podocytes. Similarly, SQ exerted a protective effect against ADR-induced podocyte injury by inhibiting apoptosis. Furthermore, inhibition of the ERK/CK2-α/β-catenin pathway-mediated epithelial-to-mesenchymal transition (EMT) was found to be involved in the anti-apoptotic effect of SQ in PHN rats and podocytes, marked by the reduction in vimentin and α-SMA and the induction of Synaptopodin and Podocin protein levels.ConclusionInhibition of EMT via the ERK/CK2-α/β-catenin pathway may be the main mechanism by which SQ suppresses podocyte apoptosis in IMN.